Skin game [compact disc, unabridged] : a novel of the Dresden files - Butcher, Jim, 1971- (Butcher, Jim, 1971- Dresden files., 2014)
Mab has just traded Harry's skills to pay off one of her debts. And now he must help a group of supernatural villains, led by one of Harry's most dreaded and despised enemies, Nicodemus Archleone, to break into the highest-security vault in town so that they can then access the highest-security vault in the Nevernever. It's a smash-and-grab job to recover the literal Holy Grail from the vaults of the greatest treasure hoard in the supernatural world, which belongs to the one and only Hades.